2017
DOI: 10.1002/ijc.30875
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and breast cancer risk: A prospective nested case–control study on serum selenium levels, smoking habits and overweight

Abstract: Previous research has not been conclusive regarding the association between selenium (Se) and breast cancer. This study was conducted to clarify if there is an association between prediagnostic serum Se levels and breast cancer risk. A population based cohort, the Malmö Diet and Cancer Study, was used and linked with the Swedish cancer registry up to 31 December 2013. Our study included 1,186 women with breast cancer and an equal number of controls. Selenium levels were analysed from stored serum samples. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…With respect to breast cancer, prospective studies have generally reported no association between blood or toenail selenium levels and risk [9, 2023]. In our study, breast cancer was the most commonly diagnosed cancer, followed by cancers of the lung and colon.…”
Section: Discussionmentioning
confidence: 38%
“…With respect to breast cancer, prospective studies have generally reported no association between blood or toenail selenium levels and risk [9, 2023]. In our study, breast cancer was the most commonly diagnosed cancer, followed by cancers of the lung and colon.…”
Section: Discussionmentioning
confidence: 38%
“…Selenium (Se) has been studied regarding a protective effect against breast cancer risk and these studies have rendered mixed but mainly null results 1,2 . Our results from a previous study, as well as a recent Cochrane systematic review, suggest that it is unlikely that Se is associated with the overall risk of breast cancer 2,3 . However, two studies have reported increased breast cancer mortality among women in the lowest quartile of serum Se as well as Se intake, and thus a potential protective effect of Se might be seen in clinical outcome rather than in incidence 4,5 …”
Section: Introductionmentioning
confidence: 72%
“…As previously described by Sandsveden et al [2], the saved serum was analyzed by ALS Scandinavia AB, Luleå, Sweden. A total of 262 women lacked the necessary amount of stored serum and therefore could not be included in the analyses.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…We have previously reported on the association between pre-diagnostic serum selenium and breast cancer risk [2]. The aim of the current study was to examine breast cancer risk related to pre-diagnostic levels of dietary intake of selenium within MDCS.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation